Pengaruh CR, DAR, dan DER Terhadap ROA pada Perusahaan Sub Sektor Asuransi Terdaftar di BEI - Dewi Astuti; Nisfu Fhitri (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study analyzes the effect of Current Ratio (CR), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) on Return on Asset (ROA) in insurance sub-sector companies listed on the Indonesia Stock Exchange during 2021-2024. Profitability in insurance companies is important to examine because this sector has characteristics related to risk management, claim obligations, liquidity needs, and financing structures that differ from non-financial companies. This research applies a quantitative approach with a causal associative method. The data used are secondary data obtained from annual financial statements published on the website of the Indonesia Stock Exchange. The population consists of 19 insurance companies, while the sample was selected using purposive sampling, resulting in 9 companies and 36 observations. Data were analyzed using multiple linear regression with SPSS 27, preceded by assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that CR has no significant effect on ROA, suggesting that liquidity is not the main factor in improving profitability among insurance companies. DAR has a positive and significant effect on ROA, indicating that assets financed by debt can support profit generation when managed productively. DER has a negative and significant effect on ROA because dependence on debt compared with equity may increase financial expenses and reduce profitability. Simultaneously, CR, DAR, and DER have a significant effect on ROA. The Adjusted R Square value of 0.275 indicates that 27.5% of ROA variation is explained by the three independent variables, while 72.5% is affected by other outside factors.